التعسف في استعمال الحق في تأديب الزوجة المسلمة في شمال غرب الصين: واقعه، وصوره، وأسبابه، وعلاجه: Abuse of the Right to Discipline a Muslim Wife in Northwest China: Its Reality, Form, Causes, and Remedy - Li, HaiLing; El Saifi, Houssam El Din (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص يدرس هذا البحث التعسف في استعمال الحق في تأديب الزوجة المسلمة في شمال غرب الصين: أسبابه وعلاجه، تكمن مشكلة البحث في أنَّ كثيرًا من مسلمي الصين لا يعرفون الأحكام المتعلقة بالأسرة في ضوء الفقه الإسلامي، فيقع منهم التعسف في استعمال حقوقهم تجاه الزوجة المسلمة. هذا البحث يوضح مكانة المسلمة المتزوجة في الأسرة، ويبين التعسف في تأديب الزوجة المسلمة وأسبابه، وواقعه، وصوره، وأسبابه والحلول المقترحة لعلاجه في المنطقة. اعتمد البحث على المنهج الاستقرائي والمنهج التحليلي، ووظف الدراسة الميدانية في دراسة محاور البحث. قد توصل البحث لنتائج أهمها: أن العنف الأسري موجودا بشكل عام، إلا أن الرأي العام التقليدي لا يعتبره عنفا، قد يؤدي إلى سوء معاملتها. يرجع أهم الأسباب إلى عدم معرفة الأحكام الشرعية الإسلامية عند جمهور مسلمي المنطقة، وقلة بيان صور التعسف في استعمال حق القوامة في معاملة الزوجة، بل تعتبرها التوجيهات فقط. وأوصت الدراسة بإبراز هذا الملف بعمل علماء ودعاة الصين على دراسة أحوال المجتمع المسلم الصيني تجاه الأحكام الشرعية، وإعداد طلاب العلم على مستوى عالي من الفهم بالشريعة والواقع، ليكونوا قدوة حسنة للجمهور. Abstract This research studies the abuse of the right to discipline a Muslim wife in China: its causes and treatment. The problem of the research is that many Chinese Muslim husbands do not know the provisions related to the family in the light of Islamic jurisprudence. The study reached the most important results: that domestic violence exists in general, but the traditional public opinion does not consider it violence, which may lead to its mistreatment. The most important reasons are due to the lack of knowledge of Islamic legal rulings among the Muslims of the region, and the lack of explanation of the forms of abuse in the use of the right of guardianship in the treatment of the wife. Rather, the directives consider them only. The study recommended highlighting this file with the work of Chinese scholars and advocates to study the conditions of the Chinese Muslim community towards Sharia rulings, review the defect in the case, and raise their awareness of the principles and purposes of Sharia. And preparing students of science at a high level of understanding of Sharia and reality, to be a good role model for the public.